2009
DOI: 10.1603/029.102.0521
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Fertilization for Cut Roses: Effect on Crop Productivity and Twospotted Spider Mite Abundance, Distribution, and Management

Abstract: Fertilization reduction could be a useful pest management tactic for floriculture crops if it reduced pest populations with little loss in crop yield and quality. We evaluated the response of the twospotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), to different fertilization levels for cut roses, Rosa hybrida L. 'Tropicana' and quantified fertilization effects on (1) management of T. urticae on roses, (2) abundance and distribution of T. urticae on roses, and (3) yield and quality of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
1
19
0
7
Order By: Relevance
“…En primavera de 2010 la temperatura promedio fue muy similar production cycles attributed to an increase in them. Another environmental factor that can affect mite population growth is the fertilization of the plant (Chow et al, 2009;Flores et al, 2011).…”
Section: Variables Ambientales Asociadas Al Desarrollo Poblacional Dementioning
confidence: 99%
See 3 more Smart Citations
“…En primavera de 2010 la temperatura promedio fue muy similar production cycles attributed to an increase in them. Another environmental factor that can affect mite population growth is the fertilization of the plant (Chow et al, 2009;Flores et al, 2011).…”
Section: Variables Ambientales Asociadas Al Desarrollo Poblacional Dementioning
confidence: 99%
“…Otro factor ambiental que también puede afectar el crecimiento poblacional del ácaro es la fertilización de la planta (Chow et al, 2009;Flores et al, 2011).…”
Section: Variables Ambientales Asociadas Al Desarrollo Poblacional Deunclassified
See 2 more Smart Citations
“…They found that the leaf content of phosphorous in cut roses (Rosa hybrida L) increased in response to increased nitrogen fertilization, but this increase did not cause significant increase in population densities of spider mites. However, Chow et al (2009) found that spider mite densities were positively correlated with levels of nitrogen fertilization. Chen et al (2007) found a positive correlation between nitrogen and phosphorous concentrations in three foliage strata of ivy geranium, Pelargonium peltatum (L.) and within-plant distribution of spider mites.…”
Section: Introductionmentioning
confidence: 95%